Differences in knee adduction moment between healthy subjects and patients with osteoarthritis depend on the knee axis definition - Meireles, S.; De Groote, F.; Van Rossom, S.; Verschueren, S.; Jonkers, I. (Gait & posture, 2017)
•Excessive KAM in patients with knee OA depends on the knee axis definition.•Caution is required when comparing KAM from different studies on knee OA patients.•Functional axis under weight-bearing accounts for load-dependent knee instability. This study, firstly, investigates the effect of using an anatomical versus a functional axis of rotation (FAR) on knee adduction moment (KAM) in healthy subjects and patients with knee osteoarthritis (KOA). Secondly, this study reports KAM for models with FAR calculated using weight-bearing and non-weight-bearing motion. Three musculoskeletal models were created using OpenSim with different knee axis of rotation (AR): transepicondylar axis (TEA); FAR calculated based on SARA algorithm using a weight-bearing motion (wFAR) and a non-weight-bearing motion (nwFAR). KAM were calculated during gait in fifty-nine subjects (n=20 healthy, n=16 early OA, n=23 established OA) for all models and groups. Significant differences between the three groups in the first peak KAM were found when TEA was used (p=0.038). However, these differences were no longer present when using FAR. In subjects with established OA, KAMs were significantly reduced when using nwFAR compared to TEA models but also compared to wFAR models. The presence of excessive KAM in subjects with established KOA showed to be dependent on the definition of the AR: anatomical versus functional. Therefore, caution should be accounted when comparing KAM in different studies on KOA patients. In patients with end-stage knee OA where increased passive knee laxity is likely to exist, the use of weight-bearing motions should be considered to avoid increased variability in the location and orientation of a FAR obtained from activities with only limited joint loading.